The poly-traumatized patient with fractures a multi-disciplinary approach - Pape, Hans-Christoph 1962-; Sanders, Roy (Roy W.); Borrelli, Joseph (Springer, 2011)
This guide provides practical information for the care of patients with blunt injuries. It covers the care for truncal injuries (head, chest, abdomen) and fracture care of the extremities, the pelvis and the spine in a condensed fashion. Unlike previous, anatomically oriented outlines, this combines the anatomic location with frequent injury combinations. It is written for orthopedic and trauma surgeons, offering them a condensed outline of fracture treatment. In addition, all aspects of trauma care are covered, including associated injuries that may alter the decision making in patients with polytrauma.